A retrospective video analysis of canonical babbling and volubility in infants later diagnosed with childhood apraxia of speech. - Overby, Megan; Belardi, Katie; Schreiber, James (Clinical Linguistics & Phonetics, 2020)
Canonical babbling and volubility are common indicators of infant vocal development. If either indicator falls below values found in typical infants, it may be an early signal of a developmental disorder. The aim of this retrospective investigation was to examine home videos for the frequency of canonical babbles, age of canonical babbling onset, and overall volubility of eight infants later diagnosed with childhood apraxia of speech and compare these data to that of six typically developing infants as well as four infants later diagnosed with a speech sound disorder. Results revealed the infants later identified with childhood apraxia of speech used fewer canonical babbles, had later onset of canonical babbling, and fewer syllables per minute (volubility) than the comparison groups. These results suggest that infants later diagnosed with childhood apraxia of speech may be less adept in vocal exploration and in the production of canonical babbles, perhaps due to fewer opportunities for mapping articulatory movement with auditory speech sound outcomes.